Patients' perceptions of mortality risk for localized prostate cancer vary markedly depending on their treatment strategy. Issue 4 (19th April 2016) - Kendel, Friederike; Helbig, Lukas; Neumann, Konrad; Herden, Jan; Stephan, Carsten; Schrader, Mark; Gaissmaier, Wolfgang
Abstract : Treatment choice for localized prostate cancer (PCa) is a controversial issue, and mortality risk is probably the most decisive factor in this regard. The study aimed to compare prostate‐cancer‐specific mortality risk estimates for different treatment options assigned by patients managed with active surveillance (AS), radical prostatectomy (RP) and patients who had discontinued AS (DAS). Patients initially managed with AS or RP ( N = 370) were matched according to length of therapy. All patients completed mailed questionnaires assessing their mortality risk estimates (in %) and prostate‐cancer‐specific anxiety. Differences in risk estimates among the three treatment groups were analyzed using ANOVA, relationships of clinical and psychosocial variables with risk estimates using standard multiple regression. In all treatment groups, the prostate‐ cancer‐specific mortality risk was overestimated. This applied whether it was the patient's own treatment or the alternative treatment option. RP patients assigned a mortality risk to AS that was almost three times higher than that assigned to RP (50.9 ± 25.0 vs . 17.8 ± 19.7, d = 1.48; p < 0.001). Anxiety was significantly associated with risk estimates for AS ( p = 0.008) and RP ( p = 0.001). Compared with clinical data that suggest that the prostate‐cancer‐specific mortality risk for AS is low and does not significantly differ from that for RP, patients strongly overestimated the mortality risk. This was most markedly so in RP patients, who drastically overestimated the benefits of RP compared to the risk of AS. This overestimation could increase overtreatment and should therefore be corrected by better patient education. Abstract : What's new? Patients with localized prostate cancer typically must choose between invasive treatments, like radical prostatectomy (RP), and less‐invasive strategies, including active surveillance (AS). It is probable that the strategy chosen is the one patients think is most likely to minimize risk of death. However, communicating risk probabilities to patients is a great challenge. Here, men on AS and after RP were asked to rate the risk of dying from localized prostate cancer. The results show that all men, irrespective of the chosen treatment, overestimated prostate cancer mortality risk by 20–50 absolute percentage points. The findings indicate a need for better patient education.